Water Consumption and its Determinants Among Women in Ghana: 2008 Demographic and Health Survey - Clement Kubreziga Kubuga; Ambrose Atosona; Victor Mogre (European Scientific Journal, ESJ, 2019)
Water is one of the most critical nutrients for humans in ensuring good health and well-being. Interestingly, majority of the vulnerable subpopulations of women in Ghana do not meet the daily recommended water intake set by the Ghana’s Ministry of Health yet the socio-economic/ demographic factors and dietary patterns influencing water intake are lacking. This study investigated the socio-economic/ demographic factors and dietary patterns influencing water intake. A total of 1,548 women with water and food intake data from the 2008 Ghana Demographic Health Survey (GDHS), which is a representative nationwide cross-sectional study, was used. 83% of the women did not meet the recommended daily water intake. Of four dietary patterns (‘Beverage & sugary based’, ‘Meat based’, ‘Indigenous- tuber based’ and ‘Indigenous- grain based’) emerging, meat based dietary pattern, seasonality, body mass index (BMI), and alcohol consumption emerged as key determinants of water intake. In summary, seasonality, dietary patterns and some key socio-economic/ demographic factors were identified as determinants of water intake. The identified determinants can serve as a basis for nutrition intervention and policies for women in Ghana.